Patients’ opinion and perception survey of community pharmacists in Republic of Macedonia - Simonoska Crcarevska, Maja; Geskovski, Nikola; Glavas Dodov, Marija; Sterjeva, Tatjana; Karadzinska, Kristina; Slaveska Raicki, Renata (Macedonian Pharmaceutical Association, 2018)
Over the past decade, numerous changes have taken place across the community pharmacy (CP) sector in the Republic of Macedonia (RM). The overall aim of this study is to analyze patients` perception and opinion regarding the Community pharmacy sector and its recognizable role in health care system in RM. Additionally, this study focusses on factors affecting patients` choice of the certain CP and perception of the quality of the CP premises. The survey covered randomly selected patients of those visiting community pharmacies in all 8 regions of the country. An anonymous semi-open questionnaire consisting of 21 items was structured, which covered three main groups of questions related to: socio-demographic factors of the respondents, reasons influencing respondents` choice of the certain CP and respondents’ opinion and impressions of community pharmacists` expertise and quality of offered services in CP settings. The obtained results have confirmed that 69.82% of respondents showed loyalty to the same CP. These findings were supported by tree main reasons: (1) the pharmacist and professional staff working in certain CP (74.19%), (2) CP keeps up a satisfactory supply (69.68%) and (3) CP is situated in a convenient location (61.94%). The overall patients’ perception of elements of pharmaceutical care services provided in CP was that they are on a high level (above 80%). Despite the encouraging results obtained, this study can serve as a core element for continuous monitoring and quality improvement of the national CPs network in near future. Keywords: community pharmacists, pharmaceutical care, patients’ opinion and perception